2015
DOI: 10.2754/avb201585010077
|View full text |Cite
|
Sign up to set email alerts
|

Intensive training technique utilizing the dog’s olfactory abilities to diagnose prostate cancer in men

Abstract: Carcinoma of the prostate is a commonly occurring malignant tumour in men and is a common cause of death. Early diagnosis and therapy is crucial for the successful treatment of this serious disease. It is therefore desirable to develop a sufficiently reliable, minimally invasive, and inexpensive method of diagnosing prostate cancer, which would usefully supplement the diagnostic techniques currently in common use (digital rectal examination, measuring the prostate-specific antigen level in serum, transrectal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…The study demonstrated that a specially trained dog can detect PCa from urinary specimens with a sensitivity and specificity of 91%. Similar results have been achieved in our pilot study (sensitivity of 93.5% and specificity of 91.6%) 3 and in a study by Taverna et al . who used two dogs and reached a sensitivity of 98.6–100% and a specificity of 97.6–98.7%.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The study demonstrated that a specially trained dog can detect PCa from urinary specimens with a sensitivity and specificity of 91%. Similar results have been achieved in our pilot study (sensitivity of 93.5% and specificity of 91.6%) 3 and in a study by Taverna et al . who used two dogs and reached a sensitivity of 98.6–100% and a specificity of 97.6–98.7%.…”
Section: Discussionsupporting
confidence: 93%
“…Our study was performed in regard to the excellent results of our sniffer dog in detecting PCa from the 2015 study 3 and the fact that urinary sarcosine appears to be a potential PCa biomarker, whose concentrations are increased in the urine of PCa-diagnosed patients 10 , 16 . Because we are using an animal as a “sensory device”, several issues should be mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations